Facilitating the Conversation: The 2012 U.S. Presidential Election and Public Diplomacy Through Social Media. (November 2013) - Hayden, Craig; Waisanen, Don; Osipova, Yelena
The elections of president Barack Obama in 2008 and 2012 provided pivotal moments in U.S. relations with foreign publics. Examining the kind of communication cultivated between public diplomacy practitioners and publics, this article focuses on social media discourse about the 2012 U.S. election posted to U.S. diplomacy efforts on Facebook. We analyze information generated by U.S. embassy sites in Bangladesh, Egypt, and Pakistan to understand the qualities of the communication engendered by these public diplomacy overtures, the nature of public argument via the media platform, and how the election served as a process to further contemporary U.S. public diplomacy. We found that the discussion that took place in response to the announcement of Obama's reelection did not resemble a deliberative forum for debating U.S. foreign policy or regional implications. Rather, much of the messaging on these sites constituted what we term "spreadable epideictic." Implications are charted for research and practice.